Growth Diagnostics for a Resource-Rich Transition Economy : The Case of Mongolia - Ianchovichina, Elena; Gooptu, Sudarshan (World Bank, Washington, DC, 2012)
This paper uses a growth diagnostics approach à la Hausmann, Rodrik, and Velasco (HRV) to identify the most 'binding' constraints to private sector growth in Mongolia - a small, low-income, mineral-rich, transition economy. The approach of applying the HRV methodology is useful in those cases where a lack of data prevents us from estimating shadow prices to identify the most 'binding' constraint to growth. We find that although Mongolia is not liquidity constrained and has grown rapidly in recent years, economic growth has been narrowly based. Investment has flowed mainly into a small number of firms operating in mining and construction. The low level of private investment in sectors outside mining and construction has been due to low returns - a result of costly and unreliable transportation services; lengthy and complex transit procedures, including customs and trade rules; distortionary taxes; coordination failures, at both domestic and international levels; and growing corruption. Poor financial intermediation is also a problem that has kept the cost of finance high, although lower than in previous years. Alleviating these binding constraints will ensure that Mongolia maintains the path towards sustained, broad-based growth.